-7=5(4x+3)-2

Simple and best practice solution for -7=5(4x+3)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7=5(4x+3)-2 equation:


Simplifying
-7 = 5(4x + 3) + -2

Reorder the terms:
-7 = 5(3 + 4x) + -2
-7 = (3 * 5 + 4x * 5) + -2
-7 = (15 + 20x) + -2

Reorder the terms:
-7 = 15 + -2 + 20x

Combine like terms: 15 + -2 = 13
-7 = 13 + 20x

Solving
-7 = 13 + 20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20x' to each side of the equation.
-7 + -20x = 13 + 20x + -20x

Combine like terms: 20x + -20x = 0
-7 + -20x = 13 + 0
-7 + -20x = 13

Add '7' to each side of the equation.
-7 + 7 + -20x = 13 + 7

Combine like terms: -7 + 7 = 0
0 + -20x = 13 + 7
-20x = 13 + 7

Combine like terms: 13 + 7 = 20
-20x = 20

Divide each side by '-20'.
x = -1

Simplifying
x = -1

See similar equations:

| -8x-6=-6x-12 | | y=-0/4+1 | | 3(2x-5)=x-45 | | 4(4x-14)+x=5x-20 | | 5x+15=-3x-49 | | x/4-5=27 | | 3+4(n+2)=2n+3(n+4) | | x(x-15)=3(x-27) | | 0.67x+3.0=0.84x | | 23+2b=3(b+8)-3 | | 2(5x-4)=6x+12 | | -0/4+1= | | 5(5x-4)=-9x+2 | | -4y-2(4-3y)=3(y-4) | | 8(x+4)+5=101 | | 5x-2(3+x)=2(x+2) | | -6x-8+2=4x+20 | | 2(5)(3)= | | 2(x-9)+12=19 | | 2xy+7xy+5xy= | | 3(5x+2)-x=2(x-3) | | 3X=9X+3 | | -5/11+5/22= | | (-7b^2+12)+(-10b^2+4)= | | 6x+12=3x-24 | | 8x-5=-4x+19 | | -20z-0.6=30z+1.3 | | 7(100+10)= | | w-38-34=-21 | | c-6=-9 | | 17x-7=2-x | | 9x-77=2x |

Equations solver categories